MANAGEMENT OF PARAPARESIS DEVELOPED AFTER SPINAL TUBERCULOSIS THROUGH AYURVEDA- A CASE STUDY - Bohra, Mohita (International Journal of Ayurveda and Pharma Research, 2020)
Spinal tuberculosis is one of the most dangerous and destructive form of tuberculosis. Predisposing factors for spinal TB are same as that of pulmonary TB, which include poverty, overcrowding, illiteracy, malnutrition, diabetes mellitus, HIV infection, alcoholism, drug abuse. Though TB of cervical spine is rare but neurological deficits are more common as compared to lumbar spine. This is a case of 9 year old male child who developed neurological deficits after TB cervical spine. Panchakarma therapy along with oral medicines given for duration of one year provided significant relief in symptoms as- generalized weakness, muscle rigidity, muscle weakness. Further continuation of treatment is expected to bring more benefit.